PENGARUH HARGA DAN PROMOSI TERHADAP MINAT KONSUMEN TIANG BETON PADA PT. SENTOSA SAKTI MAKMUR SURABAYA - Dita Indah Sari; Sugiharto; Achmad Daengs GS (Jurnal Mahasiswa Manajemen dan Akuntansi, 2022)
This study is useful to determine the effect of prices and promotions given to consumer buying interest at PT. Sentosa Sakti Makmur Surabaya. The population in this study amounted to 50 respondents, while the sampling technique used the census method because the population and sample were the same, and the data collection technique used was a questionnaire, while the data analysis technique used the explanatory research method using statistical analysis with regression, correlation, and determination testing. and hypothesis testing. The results of this study that price has a significant effect on consumer buying interest, hypothesis testing is obtained t count > t table or (2.790> 2.012). Promotion has a significant effect on consumer buying interest, hypothesis testing is obtained t count > t table or (4,571>2,012). Price and promotion simultaneously have a significant effect on consumer buying interest with the regression equation Y= 0.471+0.315X1+0.430X2+0.28e, hypothesis testing is obtained F count > F table (60.301> 3.195).